Gender Gaps in Perceptions of Political Science Journals. Issue 1 (January 2020) - Brown, Nadia E.; Horiuchi, Yusaku; Htun, Mala; Samuels, David
ABSTRACT: The gender publication gap puts women at a disadvantage for tenure and promotion, which contributes to the discipline's leaky pipeline. Several studies published in PS find no evidence of gender bias in the review process and instead suggest that submission pools are distorted by gender. To make a contribution to this important debate, we fielded an original survey to a sample of American Political Science Association members to measure participants' perceptions of political science journals. Results reveal that the gender submission gap is accompanied by a gender perception gap at some but not all political science journals we study. Women report that they are more likely to submit to and get published in some journals, whereas men report as such with regard to other journals. Importantly, these gaps are observed even among scholars with the same methodological (i.e., quantitative or qualitative) approach.